The Effect of Shopping Lifestyle, Website Quality, and Sales Promotion on Online Impulsive Buying Skincare Skintific - Meirida, Rosi; Nuvriasari, Audita (LifeSciFi, 2024)
This research aims to determine and analyze the influence of shopping lifestyle, website quality, and sales promotions on online impulsive buying of Skintific skincare. The sample in this study is 100 people who are users and buyers of Skintific skincare products through the Shopee marketplace who live in Yogyakarta. Data collection was carried out by distributing questionnaires. The test results of this research instrument stated that the data in this study was proven to be valid and reliable in the validity and reliability tests. The classical assumption test produces a regression model that does not occur multicollinearity, does not occur heteroscedasticity, and the data is normally distributed. The results of the research show that the shopping lifestyle has a positive and significant effect on impulse purchases of Skintific skincare online. Website quality does not have a significant effect on impulse purchases of Skintific skincare online. Sales promotions have a positive and significant effect on impulse purchases of Skintific skincare online.